Tinjauan Gender: Kebahagiaan Pernikahan pada Pasangan yang Menikah Melalui Ta’aruf : Penelitian - Sulis Mariyanti; Lita Patricia Lunanta; Safitri (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Ta’aruf is a premarital process in Islam that emphasizes a brief introduction between prospective spouses under the supervision of a trusted mediator, with interactions limited in accordance with Islamic principles. Despite the relatively short period of acquaintance, couples who marry through ta’aruf still aspire to achieve happiness in their marriage. This study aimed to examine differences in marital happiness between men and women who married through the ta’aruf process. A quantitative approach with a comparative design was employed. The participants consisted of 104 individuals, including 52 men and 52 women, selected using purposive sampling. Data were collected using a marital happiness scale comprising 47 valid items, with a Cronbach’s alpha reliability coefficient of 0.979. Data analysis was conducted using an independent samples t-test. The results indicated no significant difference in marital happiness between men and women (p = 0.217; p > 0.05). These findings suggest that marital happiness among couples who marry through ta’aruf is not influenced by gender differences, but is more likely associated with other factors such as shared values, commitment, and the quality of the marital relationship.